2011
DOI: 10.1007/s12262-011-0384-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of Severe Acute Pancreatitis

Abstract: Severe acute pancreatitis (SAP) develops in about 25% of patients with acute pancreatitis. Severity of acute pancreatitis is linked to the presence of systemic organ dysfunctions and/or necrotizing pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
0
18
0
1
Order By: Relevance
“…In addition, broad spectrum antibiotics with good tissue penetration are necessary to prevent infection in SAP after CT-proven pancreatic necrosis 66 . Patients suffering from infected necrosis, massive hemorrhage, bowel perforation, sterile necrosis with clinical deterioration or symptomatic organized necrosis are usually indicated for surgical intervention 67 . Experimental animal studies, have reported the protective effects of dexamethasone on multiple organ injury in rats with SAP.…”
Section: Treatment Of Underlying Disease (Sap)mentioning
confidence: 99%
“…In addition, broad spectrum antibiotics with good tissue penetration are necessary to prevent infection in SAP after CT-proven pancreatic necrosis 66 . Patients suffering from infected necrosis, massive hemorrhage, bowel perforation, sterile necrosis with clinical deterioration or symptomatic organized necrosis are usually indicated for surgical intervention 67 . Experimental animal studies, have reported the protective effects of dexamethasone on multiple organ injury in rats with SAP.…”
Section: Treatment Of Underlying Disease (Sap)mentioning
confidence: 99%
“…It occurs in about 15-20 % of all cases of acute pancreatitis (AP) and is considered the most serious disease course due to high complications and death rates despite recent diagnostic and therapeutic advancements; the mortality may be particularly high if necrotic areas become infected, exceeding 50 % when infection and persistent organ failure develop during the first week of the illness (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…In the light of these facts, taking also into account variable and unpredictable course of AP, current recommendations emphasize appropriate early management based on careful initial risk assessment in all patients presenting with AP on admission to hospital (1,4). Dealing with this issue, previous studies have identified numerous factors that are only associated with or may contribute to the development of severe disease and increased mortality rate in patients with AP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 20-25% of patients with acute pancreatitis develop severe acute pancreatitis (SAP), which tends to be complicated by systemic inflammatory response syndrome (SIRS), with a high mortality rate >30% (1)(2)(3). SIRS is an early manifestation of multiple organ dysfunction syndrome and multiple organ failure.…”
Section: Introductionmentioning
confidence: 99%